Research on classroom teaching strategies for junior high school students under the guidance of core literacy - Zhong, Yujiao; Pereira, Jerito (Pi Radian: Journal of Mathematics Education, 2024)
Student-oriented classroom is the fertile ground for students to develop core literacy of mathematics. The new curriculum standard emphasizes the teaching concept of "student-oriented". In the teaching activities, teachers should give full play to the subject status of students, return the classroom to students, so that students can better show themselves, so that they can master mathematical knowledge and develop the core literacy of mathematics subject naturally. However, at present, the classroom atmosphere of some middle school mathematics students' classroom reform pilot middle schools has not reached the ideal effect. There are some problems in the teaching classroom, such as ignoring students' main position, ignoring students' initiative in learning, and teachers' student-oriented concept is not thorough enough. This paper aims to develop students' core literacy. By studying the current situation of the mathematics students-based classroom in junior middle school and putting forward strategies to solve the problems, the teaching mode of the student-oriented classroom is improved.